(untitled) - Steve Flinders (Oxford, 1999)
What is the story behind the gold medals? - an Olympic gold medal. The best prize any athlete can ever win. - We see their winners every four years on our televisions, but who are they, and how do they get there? And what is the story behind the Games? How did they start and how they grown? This book tells us some of the answers.
Keywords: almanacs,curiosities and wonders